An Analysis Of The Conflict Faced By The Main Characters In Laskar Pelangi Film - Anggraini, Melia; Pradana, Ami; Rahman Putra, Aziiz (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This study analyzes the conflicts faced by the main characters in the film "Laskar Pelangi", set in the 1970s on the Bangka Belitung Islands. The film portrays aspects of life such as economic limitations, moral values, friendship, family dynamics, and the importance of quality education. Using semiotic and structuralist approaches, the study examines the symbols and narrative structures influencing the audience's understanding of these conflicts. The research found that internal conflict (Man vs Self) is the most dominant, accounting for 42% of the total conflicts. External conflicts include "Man vs Society" (32%), "Man vs Man" (18%), "Man vs Nature" (7%), and "Man vs Fate" (1%). Internal conflicts illustrate the characters' personal struggles, while external conflicts highlight societal and environmental challenges. The study also emphasizes the importance of friendship and moral support in overcoming life's difficulties. Character relationships in the film serve as pillars of strength in facing various issues. Through in-depth analysis, this research aims to provide new insights into the dynamics of conflict in film narratives and the film's contribution to teaching moral values and perseverance.